History of the dental elevator - Forrai, Judit; Spielman, Andrew I. Spielman (Kaleidoscope (Budapest), 2024)
Dental elevators have been used for at least 1,000 years and are still widely utilized in dentistry today, from routine tooth extractions to more complex procedures performed by oral and maxillofacial surgeons.